Peran Penyuluh Agama dalam Kehidupan Beragama guna Meningkatkan Keluarga Sakinah (Studi Kasus pada Majelis Ta'lim Al-Muhajirin Sukarame II Bandar Lampung) - Rahmat Hidayat (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
ABSTRACT Islamic Religious Instructor has a quite strategic role in the midst of society. besides he is a preacher of Islam, also the Islamic Religious Instructor, according to his function as a guide, illuminator, and community builder with religious language. The role of religious counselors in addition to functioning as an impetus for the community to actively participate in development also plays a role in overcoming obstacles that build the course of development, particularly overcoming negative impacts. Religious instructors as religious leaders always guide, nurture, and move the community to do good and stay away from prohibited acts, inviting something that is needed by the community in fostering its territory both for the purposes of social facilities and worship. The Religious Instructor is a place to ask questions and a place to complain for his community to solve and resolve with his advice. Religious Instructors as community leaders act as priests in matters of religion and social problems as well as in matters of state by an effort to succeed the government program. The role of religious instructors in improving and creating the quality of sakinah families in the Muhajirin AL Muhajirin voluntary II Ta'lim Assembly group in Teluk Betung Barat Subdistrict, Bandar Lampung City, it can be concluded that religious counselors play an important role in improving the quality of sakinah families, one of which is in terms of worship , and also able to improve the quality of a new family and has long become a sakinah family.